Mengukur Kinerja Perusahaan: Peran Firm Size sebagai Variabel Moderasi antara Current Ratio, Total Asset Turnover dan Firm Value - Hamdana; Mohamad Agus Salim Monoarfa; Meriyana Franssisca Dungga (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine how the effect of Current Ratio (CR) and Total Asset Turover (TATO) on Firm Value, in this case the Share Price with Firm Size as a Moderating Variable (Case Study of Food and Beverage Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange for the Period 2018-2022). The samples, that are 20 food and beverage sub-sector manufacturing companies, are determined through purposive sampling,. The data collection technique in this study uses secondary data obtained from financial statement data published by the Food and Beverage sub-sector manufacturing companies on the Indonesia Stock Exchange (IDX). Then, the data are analyzed using Multiple Regression Analysis and Moderation Regression Analysis methods assisted by the SPSS 16 software.The results showed that partially, Current Ratio significantly affects the Share Price, while Total Asset Turnover does not affect the Share Price. Then, Current Ratio and Total Asset Turnover simultaneously significantly affect Share Price.However, Current Ratio does not affect the Share Price moderated by Firm Size and Total Asset Turnover does not affect the Share Price moderated by Firm Size.